A DNMT3A PWWP mutation leads to methylation of bivalent chromatin and growth retardation in mice - Sendžikaitė, Gintarė (Nat Commun, 2019)
DNA methyltransferases (DNMTs) deposit DNA methylation, which regulates gene expression and is essential for mammalian development. Histone post-translational modifications modulate the recruitment and activity of DNMTs. The PWWP domains of DNMT3A and DNMT3B are posited to interact with histone 3 lysine 36 trimethylation (H3K36me3); however, the functionality of this interaction for DNMT3A remains untested in vivo. Here we present a mouse model carrying a D329A point mutation in the DNMT3A PWWP domain. The mutation causes dominant postnatal growth retardation. At the molecular level, it results in progressive DNA hypermethylation across domains marked by H3K27me3 and bivalent chromatin, and de-repression of developmental regulatory genes in adult hypothalamus. Evaluation of non-CpG methylation, a marker of de novo methylation, further demonstrates the altered recruitment and activity of DNMT3A(D329A) at bivalent domains. This work provides key molecular insights into the function of the DNMT3A-PWWP domain and role of DNMT3A in regulating postnatal growth.